Identification of genes involved in polysaccharide-independent Staphylococcus aureus biofilm formation. - Blaise R Boles; Matthew Thoendel; Aleeza J Roth; Alexander R Horswill (PLoS ONE, 2010)
Staphylococcus aureus is a potent biofilm former on host tissue and medical implants, and biofilm growth is a critical virulence determinant for chronic infections. Recent studies suggest that many clinical isolates form polysaccharide-independent biofilms. However, a systematic screen for defective mutants has not been performed to identify factors important for biofilm formation in these strains. We created a library of 14,880 mariner transposon mutants in a S. aureus strain that generates a proteinaceous and extracellular DNA based biofilm matrix. The library was screened for biofilm defects and 31 transposon mutants conferred a reproducible phenotype. In the pool, 16 mutants overproduced extracellular proteases and the protease inhibitor alpha(2)-macroglobulin restored biofilm capacity to 13 of these mutants. The other 15 mutants in the pool displayed normal protease levels and had defects in genes involved in autolysis, osmoregulation, or uncharacterized membrane proteins. Two transposon mutants of interest in the GraRS two-component system and a putative inositol monophosphatase were confirmed in a flow cell biofilm model, genetically complemented, and further verified in a community-associated methicillin-resistant S. aureus (CA-MRSA) isolate. Collectively, our screen for biofilm defective mutants identified novel loci involved in S. aureus biofilm formation and underscored the importance of extracellular protease activity and autolysis in biofilm development.